Degradasi Makna Simbolik Busana Adat Minangkabau di Kota Padang (Studi tentang Kasus-Kasus Busana Adat dalam Tari dan Penyambutan Tamu) - Asriati, Afifah (Humanus, 2011)
This study aims to determine the cause of changes in the function of Minangkabau traditional clothing into the fashion of dance and reception, and whether the changes brought to the degredation of symbolic meaning of the traditional fashion. Through a qualitative approach and techniques of documentation, interviews and triangulation, member check, and peer debriefing, it was found that there have been changes in the function of traditional clothing into the fashion of dance and reception. The reason is because of a lack of understanding of users and choreographer. It is only driven by its aesthetic value alone, without appreciate the value of philosophy in addition to the lack of supervision of customary institutions. Thus there has been a degredation of traditional symbolic value when the traditional clothing was used in dancing and reception. Key Words: degradation of Symbolic Meaning, Minangkabau Traditional Clothing, Traditional Clothing in Dance and Guests Reception.